We find the first differences between terms:
7-4=3; 12-7=5; 19-12=7; 28-19=9.
Since these are different, this is not linear.
We now find the second differences:
5-3=2; 7-5=2; 9-7=2. Then:
Since these are the same, this sequence is quadratic.
We use (1/2a)n², where a is the second difference:
(1/2*2)n²=1n².
We now use the term number of each term for n:
4 is the 1st term; 1*1²=1.
7 is the 2nd term; 1*2²=4.
12 is the 3rd term; 1*3²=9.
19 is the 4th term; 1*4²=16.
28 is the 5th term: 1*5²=25.
Now we find the difference between the actual terms of the sequence and the numbers we just found:
4-1=3; 7-4=3; 12-9=3; 19-16=3; 28-25=3.
Since this is constant, the sequence is in the form (1/2a)n²+d;
in our case, 1n²+d, and since d=3, 1n²+3.
The correct answer is n²+3
Answer:
2(4+x)
Step-by-step explanation:
"Twice the sum of" tells us it will be the equation times two
"the sum of four and a number" is easy, thats 4 + x
The second number is x because the number is not specified so we need a place holder, x in this case, to tell us that the number is not given.
All this put together = twice the sum of four and a number, or <u>2(4+x)</u>
Answer:
The function is increasing from x = -2 to x = -1.
Step-by-step explanation:
The graph starts at -2 and is increasing by 1. it would not be "The function is increasing from x = 0 to x = 1" because it does not start at 0. it starts at -2. even though they both increase by 1, the starting point answer is always the best option.
395 *25% could also be interpreted as 395/4
395 = 98.75
4